A Comparison Study of the Electrocatalytic Sulfur Reduction Activity on Heteroatom‐Doped Graphene for Li–S Battery. Issue 3 (13th January 2023) - Zhang, Wei; Li, Yifan; Lv, Haifeng; Xie, Shuai; Zhu, Jiawen; Xu, Junjie; Jin, Hongchang; Kong, Xianghua; Jin, Song; Wang, Haiyan; Wu, Xiaojun; Ji, Hengxing
Abstract : The complicated multielectron and multiphase electrocatalytic sulfur reduction reaction (SRR) occurring in the Li–S battery is demonstrated, which strongly influences the performances of this battery chemistry. Effective candidates for SRR are often based on heteroatom‐doped carbon‐based electrocatalysts. However, the electrocatalytic sulfur reduction activity of these catalysts is so far insufficiently explored. Herein, a series of graphene doped with nonmetal elements (nitrogen, phosphorus, and sulfur) are designed and synthesized. It is shown that nitrogen‐doped graphene has a superior SRR catalytic activity with highest electrochemical reversibility and best electrochemical kinetics for the liquid–solid two‐phase conversion from long‐chain soluble Li2 S x (4 ≤ x ≤ 8) and the solid‐state Li2 S2 to Li2 S conversion. The considerably improved kinetics of the liquid–solid and solid–solid phases conversion reduces the continued accumulation of lithium polysulfides in electrolyte and the passivation of the electrode, thus resulting in a significant improvement in electrochemical performance of Li–S cells. Density‐functional theory calculations demonstrates that the highest SRR performance of N/G is originated from the strongest adsorption of the sulfur species and lowest energy barriers for Li2 S decomposition among three doped graphene samples. This study is believed to guide the design of efficient electrocatalysts to exceed the performance of the benchmark for Li–S battery. Abstract : Herein, electrocatalytic activity over sulfur reduction reaction (SRR) of heteroatom‐doped graphene is investigated. Experimental and density‐functional theory calculations show that nitrogen‐doped graphene has the highest SRR performance for the conversion from long‐chain soluble Li2 S x (4 ≤ x ≤ 8) and solid‐state Li2 S2 to Li2 S due to the strongest adsorption of the sulfur species and lowest decomposition energy barriers.